Energy transfer and photoluminescence properties of lanthanide-containing polyoxotitanate cages coordinated by salicylate ligands. Issue 16 (9th April 2018) - Li, Ning; Subramanian, Gomathy Sandhya; Matthews, Peter D.; Xiao, James; Chellappan, Vijila; Rosser, Timothy E.; Reisner, Erwin; Luo, He-Kuan; Wright, Dominic S.
Abstract : The salicylate to Ti 4+ charge-transfer process and energy transfer mechanisms in a series of polyoxotitanium cages are investigated, to account for their photoluminescence properties. Abstract : Polyoxotitanate (POT) cages have attracted considerable attention recently; much of this from the fact that they can be considered to be structural models for the technologically important semiconductor TiO2 . Among the reported POT cages, lanthanide-containing (Ln-POT) cages are of particular interest owing to the fascinating luminescence properties of Ln 3+ ions and the versatile coordination environments that they can adopt. In the present study, we report the energy transfer mechanism and photoluminescence properties of a series of isostructural Ln-POT cages coordinated by salicylate ligands, of general formula [LnTi6 O3 (O i Pr)9 (salicylate)6 ] (Ln-1, Ln = La to Er excluding Pm). Both visible (forPr-1, Sm-1, Eu-1, Ho-1 andEr-1 ) and near-infrared (forNd-1 andEr-1 ) Ln 3+ -centred photoluminescence can be sensitised in solution, and most importantly, their excitation bands all extend well into the visible region up to 475 nm. With the assistance of steady-state and time-resolved photoluminescence spectroscopy, an energy-transfer mechanism involving the salicylate-to-Ti 4+ charge-transfer state is proposed to account for the largely red-shifted excitation wavelengths of theseLn-1 cages. The photoluminescence quantum yield ofNd-1 upon excitation via the charge-transfer state reaches 0.30 ± 0.01% in solution, making it among the highest reported values for Nd 3+ -complexes in the literature.